Quantiferon-TB gold in-tube performance for diagnosing active and latent tuberculosis in Malaysian population - Azmi, Liyana (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2013)
Halting the progression of active tuberculosis (TB) involves the detection ofTB from a latent stage. Currently, in-vitro interferon-gamma assays (!GRAs) are being used to detect for active TB as well as latent TB besides Tuberculin Skin Test (TST). One of IGRA used to diagnose for Latent Tuberculosis Infection (LTBI) is the QuantiFERONTB (QFT) Gold assay which measures the levels of interferon gamma stimulated by QFT peptides (CFP-10, ESAT 6 and TB7.7) in patient plasma. However, the information regarding the performance of this kit especially in Malaysian population is limited. Therefore this study aims to test for the sensitivity and specificity of the QFT kit in Malaysian population. Whole blood samples were collected from 47 confirmed TB patients, 28 high-risk TB individuals (healthy contacts) and 24 BCG vaccinated low-risk TB individuals (non-TB) and stimulated with TB antigens prior to ELISA for QFT. Specificity and sensitivity of the QFT was analysed based on known TB patients and non-TB individuals. The specificity of QFT was determined as 79.16 % among low-risk patients and the sensitivity of QFT for Malaysian population was 68.08% among confirmed TB patients. Meanwhile, the percentage of positivity for latent TB detected among high-risk TB patients was 46.42%. Our study showed comparable results to the studies conducted at other neighbouring regions such as Singapore and India. Our findings revealed that the QFT is also suitable to be used as a diagnostic kit for the detection ofTB and latent TB.